Investigation of current situation of building energy conservation in Malaysia for optimal air-conditioning design - Azizuddin, Abd Aziz; Sumiyoshi, Daisuke; Akashi, Yasunori (Kyushu University, 2013)
This paper reviews the current situation in Malaysia relating to energy consumption, indoor thermal comfort and air-conditioning system design in a hot and humid country of Malaysia. It is observed that the guideline towards low energy building was already in place. The research pertaining to comfort temperature seems to dominate the thermal comfort research while the analysis of humidity was lacking. It is observed that the air-conditioning design was made so that the system operates in relatively low temperature and humidity. The low temperature also will increase the building energy consumption. Air-conditioning design was intentionally oversized which would prevent the system running at full load and best efficiency. Simulation of building energy consumption was not carried out and leads to the selection of system merely based on equipment cost without considering the energy.